Emotional intelligence and mathematics learning interest in students’ mathematical reasoning ability - Safrianus Jehabun; Bedilius Gunur; Yohanes Kurniawan (STKIP PGRI Banjarmasin, 2020)
This study aims to determine. 1) the relationship between emotional intelligence and students' mathematical reasoning abilities; 2) understand the relationship between interest in learning mathematics with mathematical punishment abilities; and 3) understanding the simultaneous relationship between emotional intelligence and mathematics learning interest on students' mathematical reasoning abilities. The method used is correlational. The population is students of class VIII 10 Ruteng Middle School, Ruteng sub-district, Mangarai regency, NTT province, which holds 225 students. With the random technique obtained by 70 students as a sample, then using a proportional random sampling technique obtained samples from each class that is ten students. The instrument used consisted of questionnaires and description test questions. Data were analyzed using simple and multiple conversion. The results showed that; 1) There is a significant relationship between emotional intelligence with students, with a contribution of 23.3%; 2) there is a significant relationship between the interest in learning mathematics with the level of students, with a contribution of 16%; 3) there is a relationship between emotional intelligence and interest in learning mathematics with mathematical punishment, with a contribution of 30.2%.